PARKINSON’S DISEASE DEMENTIA: A COMPREHENSIVE CASE REPORT - Fitriasari, Elsye; Laksmidewi, Anak Agung Ayu Putri; Widyastuti, Ketut; Mahadewi, Ni Putu Ayu Putri (MNJ (Malang Neurology Journal), 2026)
Background: Parkinson’s disease (PD) is a progressive neurodegenerative disorder affecting 1–2% of individuals over 60 years old. Beyond motor symptoms, PD is often associated with dementia, especially with advancing age and disease duration. The risk of Parkinson’s Disease Dementia (PDD) increases markedly in older patients, reaching up to 80–90% by age 90. Key risk factors include age, severity of parkinsonism, male gender, psychiatric symptoms, and mild cognitive impairment. PDD differs from Alzheimer’s disease, with more prominent deficits in attention, executive function, and visuospatial skills. Its pathogenesis involves dopaminergic neuronal loss, α-synuclein deposition, inflammation, and oxidative stress. Case Report: A 70-year-old man with a five-year history of worsening hand tremors, gait disturbance, and bradykinesia presented with additional cognitive decline, including forgetfulness and difficulty managing daily tasks. He had a known diagnosis of PD, hypertension, and hearing impairment. Physical exam showed classic PD features, and brain MRI revealed cortical atrophy and an absent swallow tail sign. He was diagnosed with PDD, Hoehn and Yahr stage 3, and treated with pharmacologic therapy and rehabilitation. Discussion: The diagnosis of PDD in this patient was based on the Movement Disorder Society (MDS) criteria, which require pre-existing PD, gradual onset of dementia, and significant cognitive decline affecting daily function, without other identifiable causes. Cognitive testing and MRI findings supported the diagnosis. PDD is associated with neurodegeneration involving dopaminergic and other neurotransmitter systems, particularly affecting executive function and memory. Management aims to address both motor and cognitive symptoms, with cholinesterase inhibitors like rivastigmine shown to improve cognitive outcomes. Conclusion: Patients with PD may experience progression to dementia, marked by both motor and non-motor symptoms. Compared to age-matched individuals without PD, those with PD are at a substantially higher risk of developing dementia.